2017
DOI: 10.4236/wjcd.2017.78021
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Profile and Treadmill Test Relationship of Women with Chest Pain Suggestive of Coronary Artery Disease

Abstract: Aim: The aim of present study was to analyze the prevalence and pattern of coronary artery disease (CAD) among women who underwent coronary angiography (CAG) and Treadmill Test (TMT). Methods: A total of 100 consecutive women patients for coronary angiogram were studied at Department of Cardiology, Government Medical College, Kottayam, Kerala, India on over a period of 6 months from February 2008. Total 65 women completed TMT stress test. The patients were subjected to CAG and TMT. Data were analyzed by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Periyapattana and AVS from south India and Stanley suggested in their study that combined TMT and MPI in-creases the PPV to 94% and diagnostic accuracy to 88% and together performs the gatekeeper function for CAG so that optimal decision making can be achieved. 8,9 Our study showed that PPV of TMT is lower (53%) in females than in males (83%). To detect obstructive CAD by CAG, better to see the other parameters also such as age and diabetes along with high-probability TMT.…”
Section: Discussionmentioning
confidence: 54%
“…Periyapattana and AVS from south India and Stanley suggested in their study that combined TMT and MPI in-creases the PPV to 94% and diagnostic accuracy to 88% and together performs the gatekeeper function for CAG so that optimal decision making can be achieved. 8,9 Our study showed that PPV of TMT is lower (53%) in females than in males (83%). To detect obstructive CAD by CAG, better to see the other parameters also such as age and diabetes along with high-probability TMT.…”
Section: Discussionmentioning
confidence: 54%